National museum of American art. (American History)
Presents that the art and artists in the Smithsonian Institution's National Museum of American Art is presented in a CD-ROM for Macintosh and Windows. Approximate number of museum's permanent collection which featured in CD-ROM; How Elizabeth Broun, director, introduces a number of her favorite artworks; Featured artists; Other features.